1998
DOI: 10.1093/humrep/13.10.2823
|View full text |Cite
|
Sign up to set email alerts
|

The effects of twisted ischaemic adnexa managed by detorsion on ovarian viability and histology: an ischaemia-reperfusion rodent model

Abstract: This prospective controlled follow-up study was designed to examine the effects of adnexal torsion on long-term ovarian histology and radical scavenger (FRS) activity, and subsequent viability following the detorsion of twisted ischaemic adnexa, in a primate centre of a university clinic. Adnexal torsion/occlusion was created by twisting the adnexa three times and fixing on to the side wall or by applying vascular clips in cycling female rats at 70 days of age. Following an ischaemic period of 4 to 36 h, the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
99
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(108 citation statements)
references
References 10 publications
5
99
2
2
Order By: Relevance
“…All rodent adnexa undergoing surgical torsion for 24 hours displayed normal histological findings despite a black-blue, ischemic appearance immediately and for one week after reversal of the torsion. The black-blue appearance was due to an initial lymphatic and venous stasis rather than significant arterial ischemia (24). In various studies in the literature, it has been reported that ovarian function is preserved in 88% to 100% of cases after detorsion of the twisted adnexa (13,(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…All rodent adnexa undergoing surgical torsion for 24 hours displayed normal histological findings despite a black-blue, ischemic appearance immediately and for one week after reversal of the torsion. The black-blue appearance was due to an initial lymphatic and venous stasis rather than significant arterial ischemia (24). In various studies in the literature, it has been reported that ovarian function is preserved in 88% to 100% of cases after detorsion of the twisted adnexa (13,(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 98%
“…Oelsner et al demonstrated that the adnexa can retrieve its functional integrity, which was shown by the ultrasonographic observation of follicular development (91.3%), the normal macroscopic appearance of the adnexa during subsequent surgical intervention (92.4%), and successful oocyte fertilization in all reported cases (13). Taskin et al investigated adnexal recovery in rodents (24). All rodent adnexa undergoing surgical torsion for 24 hours displayed normal histological findings despite a black-blue, ischemic appearance immediately and for one week after reversal of the torsion.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of ovarian enlargement, abdominal pain, nausea, might indicate torsion of adnexa. Taskin et al 11 showed that even with complete ischemia gross appearance does not correlate with outcome and that detorsion within 24 hours did not show an increase in free radical reperfusion injury. In one of our cases inspite of hemorrhagic nature of the ovarian tissue detrosion resulted in achievement of normal functionality of the ovary.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore in pregnant women the risk of complications associated with an acute abdomen outweighs the risks associated with abdominal surgery. Additionally, early intervention can sometimes salvage torted tissue by detorsion if it is performed in time [15].…”
Section: Discussionmentioning
confidence: 99%